PENGARUH KOMITMEN ORGANISASIONAL TERHADAP SENJANGAN ANGGARAN DENGAN IDEOLOGI ETIS SEBAGAI VARIABEL PEMODERASI - HY. Sri Widodo (KINERJA, 2015)
Dysfunctional Behavior, mainly Corruption, pervasively happens in Indonesia. Business people believeÂ in â€œThe Myth of Amoral Businessâ€, in which the meaning of business is profit. The focus of business is to getmaximum profit because profit is perceived as an ultimate goal. Business people always separate business fromÂ ethical dimension.Â In budgeting, dysfunctional behavior manifests in the form of Budgetary Slack. Middle and Low levelÂ managers create slack in their budget proposals by underestimating revenues and overestimating expensesÂ intentionally. The objectives of this behavior are anticipating uncertainties and increasing bonuses.Â Dysfunctional behavior can be weakened by strengthening Ethical Ideology of managers involved inÂ budgeting. Managers with strong Ethical Ideology will behave in the best interest of the company as a whole;on the other hand, managers with weak ethical ideology will maximize their own interest in the expense ofÂ companiesâ€™ interest.The objective of this research is to examine the effects of organizational commitment on budgetary slackÂ and the role of ethical ideology in moderating these two variables. For this purpose, the data are collected fromÂ 187 middle level and top level private companyâ€™s managers via questionnaire. The result of this research showsÂ that Ethical Ideology weakens the effect of Organizational Commitment on Budgetary Slack.Keywords: organizational commitment, ethical ideology, dysfunctional behavior, budgetary slack